Penerapan e-payment Menggunakan QRIS Sebagai Inovasi untuk Mempermudah Transaksi Pada Talenta Cafe di Jalan Kasah - Kusdiana, Yayu; Zanra, Sri Wahyuni (Cahaya Pengabdian, 2024)
Talenta Cafe is an UMKM in the culinary sector located in Tangkerang Tengah Subdistrict, Marpoyan Damai District, Pekanbaru which was founded in 2021. Talenta Café is a gathering place for young people in Pekanbaru and has comfortable, safe facilities, the food and drinks offered are not too expensive in compare it with other cafes and is accompanied by live music. This development answers the problems found in Talenta Café experience deficiencies in digital payments using today's technology. Therefore, in this development a QRIS payment application will be created as a digital payment which will make it easier for Talenta Cafe to market and develop its products. This design uses interview research methods, documentation and internet literature study. The method used in this community service is training in the use of QRIS.